Belief about language learning among pre-service TESL teacher trainees in IPG / Nailah Mustaffa - Mustaffa, Nailah (2015)
This study responds to the possible changes in beliefs that teachers hold nowadays about language learning. As for a pre service teacher, the experience being a student in the 20th century would somehow influence his or her beliefs about language learning. In this respect, this study aimed to investigate the pre-service ESL teachers' beliefs about language learning and the influence of the reported beliefs with their teaching approaches. The research was conducted using a modified questionnaire based on Beliefs About Language Learning Inventory by Horwitz. It was conducted to identify the pre-service teachers' beliefs about language learning solely. Other than that, interview was also conducted to elicit information regarding their beliefs about language learning and teaching approaches. Fifty seven pre-service teachers from the Department of Languages, Institute of Teacher Education Dato' Razali Ismail Campus were selected at random for the study. Ten of them were selected for the interview survey, unfortunately on the day of the interview only two of them came for the interview due to their personal reasons. The beliefs about language learning of these pre-service teachers were collected from both data sources. Then, their beliefs were analyzed and discussed to study the relationship between the pre-service teachers' beliefs and their teaching approaches. Consequently, this study may beneficial for further research in the area of beliefs about language learning among pre-service teachers of English.